Pertanggungjawaban Para Pihak dalam Hal Terjadinya Peretasan Telepon Seluler - Ni Made Vira Vija Rahmasari; I Nyoman Putu Budiartha; Madejaya Senastri (Warmadewa Press, 2021)
With the development of the times, cell phones have become a primary need for some people with an internet that is increasingly complete with features that can support people's lives. Based on this, there are also deviant crimes that occur in society, one of which is hacking crimes against cell phones. Hacking a cell phone can create legal issues related to consumer protection. The purpose of this research is to find out what is the concept of guarantee/guarantee for the rights of consumers who use cell phones in the event of hacking and the responsibility of the government towards consumers for guarantee rights in the event of hacking of cell phones. The research method in this paper is normative legal research, with a statutory and conceptual approach. This study concludes that the warranty on hacking cases has not been regulated in the Consumer Protection Law. The form of consumer protection provided by the government to users of cellular telephone services is more directed at fostering and empowering consumers.